STRATEGI PROMOSI WISATA PULAU BAWEAN MELALUI EVENT FESTIVAL MOLOD BAWEAN - Nur Maghfirah Aesthetika (Kanal: Jurnal Ilmu Komunikasi, 2012)
This research is explanation if Molod Bawean Festival that held by Kerukunan Toghellen Bawean is appropriate with event marketing process as defined by Lynn Van Der Wagen. And then it will be seen, how event Molod Bawean Festival could be a Bawean Island tourism promotion strategy. This qualitative research is held in Bawean Island, Gresik. The research subject is the Molod Bawean Festival Head Committee and also Head of the Kerukunan Toghellen Bawean who is made the Molod Bawean Festival as an annual event. On a deeper interview that done as a data-capture technique, could be said that this Molod Bawean Festival is held with the process as defined by Lynn Van Der Wagen but still not so perfect. Using Berentang Kota Negara Benua, Molod Bawean Festival should be an effective event marketing in promoting Bawean Island Tourism if it’s held through a maximal event marketing process.